The Institution of a Referendum in the United Kingdom in the Context of the Political and Legal Fundamentals of Brexit - Вікторія Муха (Історико-політичні проблеми сучасного світу, 2021)
The article clarifies the essence and potential of the Referendum Institute in the UK in the context of the political and legal foundations of Brexit. The complexity of the subject of scientific research led to the use of an interdisciplinary approach. The article used general scientific methods of analysis and synthesis, historical and comparative methods. It has been proven that the British referendum on EU membership has provoked a lot of discussion about the expediency and consequences of Brexit. The results of the Brexit referendum will affect the transformation of the system of international relations and the formation of the international order. Brexit has many legal and constitutional aspects and problematic consequences. It has been established that referendums in Great Britain are not legally binding and the voting results are consultative, not mandatory for the country's Parliament on which the last word remains, since only the Parliament has legislative competence. In theory, representatives of the authorities could legally neglect the will of the people. Consequently, the decision to leave the EU lies not only in the plane of law, but also in politics.